Implementation of information and communication technologies for health in Bangladesh - Islam, Sheik Mohammed Shariful (Bull World Health Organ, 2015)
PROBLEM: Bangladesh has yet to develop a fully integrated health information system infrastructure that is critical to guiding policy development and planning. APPROACH: Initial pilot telemedicine and eHealth programmes were not coordinated at national level. However, in 2011, a national eHealth policy was implemented. LOCAL SETTING: Bangladesh has made substantial improvements to its health system. However, the country still faces public health challenges with limited and inequitable access to health services and lack of adequate resources to meet the demands of the population. RELEVANT CHANGES: In 2008, eHealth services were introduced, including computerization of health facilities at sub-district levels, internet connections, internet servers and an mHealth service for communicating with health-care providers. Health facilities at sub-district levels were provided with internet connections and servers. In 482 upazila health complexes and district hospitals, an mHealth service was set-up where an on-duty doctor is available for patients at all hours to provide consultations by mobile phone. A government operated telemedicine service was initiated and by 2014, 43 fully equipped centres were in service. These centres provide medical consultations by qualified physicians to patients visiting rural and remote community clinics and union health centres. LESSONS LEARNT: Despite early pilot interventions and successful implementation, progress in adopting eHealth strategies in Bangladesh has been slow. There is a lack of common standards on information technology for health, which causes difficulties in data management and sharing among different databases. Limited internet bandwidth and the high cost of infrastructure and software development are barriers to adoption of these technologies.